The Value of Human Life in the Light of Suicide Tendencies among Students in Nigerian Tertiary Institutions: Implications for Education - Greg Ekeh (CV. Tripe Konsultan, 2022)
This paper examined the value of human life in the light of suicide tendencies among students in tertiary institutions in Nigeria. Being an act of taking or terminating one’s own life, suicide remains an enigma to all pro-life humans. In the distant past, cases of suicide were not so ubiquitous in Nigeria. Its occurrence was very rare; and where it happened, it was seen as an abomination of a high order, since life was considered sacred by the people, and which no human has the right to terminate. In those days of yore, suicide was alien to the people of Nigeria and their culture. Of recent, however, suicide has become a major leading cause of mortality among students in Nigerian tertiary institutions. Inherent difficulty in predicting and ascertaining its warning signs has made accurate and specific prediction of the occurrence of suicide most elusive. Over and above this, suicide is based on personal conviction of the individual that this is the best solution to his/her problem. On that note, the effort to prevent suicide should not focus more on predictions and signs, but on certain values and implications that would convince the individual (and the society) to jettison the idea of suicide as the best solution to a perceived problem. One of such values is human life, which has some implications for education. In this direction, the paper adopted a critical analysis of concepts and literature review to explore some risk factors for suicide, its implications for education and possible solutions to suicide tendencies amongst students, especially in the tertiary institutions in Nigeria. It was discovered that suicide tendencies among tertiary institution students in Nigeria is largely due to little knowledge of the value of human life and its implications. It was therefore recommended, among others, that premium emphasis be placed on the value of human life as sacred, both in the family and formal education settings